Zum Nebensilbenvokalismus als Reflex des Entwicklungsstandes der deutschen Sprache im 17. Jahrhundert - Piotr A. Owsiński (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The article presents a linguistic analysis of a charter from the 17th century entitled “Wilkierz dla wsi klasztoru Panny Marji w Kartuzach” published by Stanisław Kutrzeba and Alfons Mańkowski in 1938 in “Archiwum Komisji Prawniczej, volume 11”. The text of an unknown scrivener was written in New High German in the Silesian dialect, which can be proved on the basis of the legal notation. The author shows the results of his analysis demonstrating the stage of the development of the vowels in the unstressed syllables with the appropriate examples.